Binding energies of excitons trapped by ionized donors in semiconductors - dos Santos, A. S.; Masili, Mauro; De Groote, J. J. [UNESP] (American Physical Society (APS), 2001)
Using the hyperspherical adiabatic approach in a coupled-channel calculation, we present precise binding energies of excitons trapped by impurity donors in semiconductors within the effective-mass approximation. Energies for such three-body systems are presented as a function of the relative electron-hole mass σ in the range 1⩽1/σ⩽6, where the Born-Oppenheimer approach is not efficiently applicable. The hyperspherical approach leads to precise energies using the intuitive picture of potential curves and nonadiabatic couplings in an ab initio procedure. We also present an estimation for a critical value of σ (formula presented) for which no bound state can be found. Comparisons are given with results of prior work by other authors. © 2001 The American Physical Society.